Prospects of Kiwi Production and Marketing in the Advancement of Household Economy in Dolakha District - Santoshi Malla; Lal Bista; Rojina Sapkota (Turkish Journal of Agriculture: Food Science and Technology)
This study entitled was conducted in 3 places of Dolakha district namely Boach, Jiri and Bigu. The study was conducted during 20thjuly to 6th September 2017. The main aim of this study was to find out whether kiwi farming is improving household economy of people living there (i.e. Boach, Jiri and Bigu) using various tools such as questionnaire, discussion, direct observation and review of literature. A total of 60 households were randomly selected for the study. Both male and female were found to be involved in kiwi cultivation. About 60 percent and 40 percent of respondents were male and female respectively. 20 percent respondent were illiterate, 38 percent people have primary level education, 17 percent were people having secondary and S.L.C. level education respectively, similarly, the respondent completing Inter were 8 percent. Kiwi was the major cash crop in the study area and the widely used variety in the study site was Monti. Agriculture is the major occupation followed by Government job, Business and others. 47 percent were involved in agriculture, 30 percent were involved in government job, 13 percent have Business and 10 percent follow other jobs like (Teaching, Driving, Abroad). Among 60 respondents 50 percent were cultivating kiwi in 1-5 ropani of land and minimum was 12 percent who cultivated kiwi in above 15 ropani area. Training related to kiwi cultivation was also given to the respondent. 47 percent respondents were trained in kiwi cultivation and 53 percent were not trained about it. Training was organized and conducted by DADO and some other organization who were concerned about agriculture. Kiwi was mostly sold to nearest local market by the farmers themselves. Kiwi cultivation was also helping farmers in economic part. The study shows that there is an improvement of household economy and livelihood by kiwi farming.